2015
DOI: 10.1016/j.appet.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Habitual total water intake and dimensions of mood in healthy young women

Abstract: Acute negative and positive mood states have been linked with the development of undesirable and desirable health outcomes, respectively. Numerous factors acutely influence mood state, including exercise, caffeine ingestion, and macronutrient intake, but the influence of habitual total water intake remains unknown. The purpose of this study was to observe relationships between habitual water intake and mood. One hundred twenty healthy females (mean ± SD; age = 20 ± 2 y, BMI = 22.9 ± 3.5 kg⋅m(-2) ) recorded all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…However, the association between early childhood and later life intake has never been demonstrated for drinking water, due to the scarcity of longitudinal studies assessing water intake. But if indeed drinking habits (i.e., plain water intake in particular) were sustained throughout life, children who drink little water would become adults who drink little water with potential consequences for kidney [10] and metabolic health [11,12] as well as cognitive and mood impairments [13,14]. During early childhood, the acquisition of eating and drinking behavior is mainly driven by adults since children depend upon them for the provision of food and beverages, and adults serve as role models which children copy and acquire habits from.…”
Section: Water Intake In Early Childhood: a Driver Of Sustainable Heamentioning
confidence: 99%
“…However, the association between early childhood and later life intake has never been demonstrated for drinking water, due to the scarcity of longitudinal studies assessing water intake. But if indeed drinking habits (i.e., plain water intake in particular) were sustained throughout life, children who drink little water would become adults who drink little water with potential consequences for kidney [10] and metabolic health [11,12] as well as cognitive and mood impairments [13,14]. During early childhood, the acquisition of eating and drinking behavior is mainly driven by adults since children depend upon them for the provision of food and beverages, and adults serve as role models which children copy and acquire habits from.…”
Section: Water Intake In Early Childhood: a Driver Of Sustainable Heamentioning
confidence: 99%
“…In line with our findings, a previous study reported higher amounts of ECW in relation to intracellular water in people with spinal cord injury, and a relation between muscle mass decrease and relative expansion of ECW (Tanaka et al, 2008). Another study reported total water intake in young healthy women to predict mood disturbances (Muñoz et al, 2015). Furthermore, the discrimination between TBW, ECW, and WB sheds light on the complex relationship of the body water-related parameters, the psychosocial parameters and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Water is a solvent for protein synthesis [4], and it helps the hydrolytic reactions for macronutrients [5], waste elimination [6], and thermoregulation [7,8]. Low water intake and underhydration are associated with various health issues such as increased risk of kidney disease [9,10], diabetes [11], obesity [12], and impaired cognitive function [13][14][15][16]. Children may be more susceptible to the adverse effects of underhydration [17] and may be at greater risk.…”
Section: Introductionmentioning
confidence: 99%